A Study on the prevalence of listener-interactive talk on the FM radio stations in Metro Manila. - Villegas, Maureen B.
This study about Listener Interactive Talk in FM Radio and aimed to answer the following research questions: (1) What were the reasons behind the FM radio stations' shift towards listener-interactive talk? (2) How did the audience contribute to the rising trend of listener interactive talk radio? (3) What were the contents of the on-air conversations in talk radio? The study made use of two theories: the Agenda-Setting Theory and the Uses and Gratifications Approach. The Agenda-Setting Theory is a three-part linear process that deals with media influencing the public, and the public acting upon policy. This is related to what the Uses and Gratifications Approach posits and that is the listeners of talk radio are not passive but take a proactive role in deciding how to use media in their lives. After the monitoring of various FM radio shows and interviewing disc jockeys and radio listeners, the researcher was able to arrive at the following findings: (1) People called in on radio shows in order to amuse themselves, their reason of calling being boredom. (2) Disc jockeys felt that the less talk on FM radio, the better since they knew the only purpose of FM radio that they were aware of was playing music to entertain. (3) Non-active listeners were prone to temptation to call in on a radio station because they felts that they can make an improvement on the quality of talk that they hear. With these findings in mind, the researcher recommends proper management of the content of on-air discussions. The researcher also proposes strict maintenance of the ongoing strategies of radio stations to balance their programming.